The Content of Cooperation between the Mahalla Institute and the Higher Educational Institutions in Terms of Globalization - Khayrixon Raxmatova (Research Parks Publishing LLC, 2021)
Mahalla, being a unique socio-territorial unit, plays an important role in educating youth in accordance with the rich life experience of elderly people. Therefore, with the help of rich experience of mahalla residents an effective pedagogical influence on young people can be provided. To increase the educational influence of mahalla on young people, cooperation between mahalla and higher educational institutions of the country should be achieved. Within the framework of such cooperation, the universities will offer methodological assistance to mahallas in conducting spiritual and educational events. The article discusses the issue that in the context of globalization there is a need to organize cooperation between higher educational institutions and institute of mahalla in several areas.